Investigation of an outbreak of COVID-19 among U.S. military personnel and beneficiaries stationed in the Republic of Korea, June-July 2021. - Shilpa Hakre; Evelyn Y Lam; Irina Maljkovic-Berry; Jun Hang; Luis A Pow Sang; Elizabeth J Bianchi; Christian Fung; Jay Gandhi; Marcus Chibucos; Matthew A Conte; Adam R Pollio; Christine A Mariskanish; et al. (Public Library of Science (PLoS), 2022)
On 28 May 2021, leisure travel restrictions in place to control coronavirus disease 2019 (COVID-19) were eased among vaccinated U.S. military personnel and beneficiaries stationed in South Korea (USFK) allowing access to bars and clubs which were off limits. We describe results from an investigation of the largest severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak as of November 2021 among USFK personnel following this change in policy. Data such as SARS-CoV-2 real-time polymerase chain reaction (RT-PCR) test results, demographic characteristics, symptom and vaccination histories, and genome sequences were analyzed. Of a total 207 new cases of COVID-19 diagnosed among USFK members from 15 June to 27 July 2021, 113 (57%) eligible cases were fully vaccinated, of whom 86 (76%) were symptomatic. RT-PCR cycling threshold values were similar among vaccinated and unvaccinated members. Whole genomic sequencing of 54 outbreak samples indicated all infections were due to the Delta variant. Phylogenetic analysis revealed two sources of SARS-CoV-2 accounted for 41% of infections among vaccinated and unvaccinated members. Vaccinated personnel were not at risk of severe illness; however, 86% experienced symptoms following infection. There were no hospitalizations among COVID-19 cases, most of whom were young military service members. Rescinded restrictions were reinstated to control the outbreak. Masking was mandated among all personnel predating U.S. national recommendations for indoor masking in high COVID-19 transmission areas. Increased vaccination with continued vigilance and extension of COVID-19 mitigation measures are warranted to contain the spread of SARS-CoV-2 variants of concern.